Maternal Choline Status, but Not Fetal Genotype, Influences Cord Plasma Choline Metabolite Concentrations. Issue 7 (13th May 2015) - Visentin, Carly E; Masih, Shannon; Plumptre, Lesley; Malysheva, Olga; Nielsen, Daiva E; Sohn, Kyoung-Jin; Ly, Anna; Lausman, Andrea Y; Berger, Howard; Croxford, Ruth; El-Sohemy, Ahmed; Caudill, Marie A; et al.
Abstract: Background: Choline deficiency during pregnancy can lead to adverse birth outcomes, including impaired neurodevelopment and birth defects. Genetic variants of choline and one-carbon metabolism may also influence birth outcomes by altering plasma choline concentrations. The effects of maternal ad libitum choline intake during pregnancy and fetal genetic variants on maternal and cord concentrations of choline and its metabolites are unknown. Objectives: This prospective study sought to assess the effect of 1 ) maternal dietary choline intake on maternal and cord plasma concentrations of choline and its metabolites, and 2 ) fetal genetic polymorphisms on cord plasma concentrations. Methods: The dietary choline intake of 368 pregnant Canadian women was assessed in early (0–16 wk) and late (23–37 wk) pregnancy with the use of a food frequency questionnaire. Plasma concentrations of free choline and its metabolites were measured in maternal samples at recruitment and delivery, and in the cord blood. Ten fetal genetic variants in choline and one-carbon metabolism were assessed for their association with cord plasma concentrations of free choline and its metabolites. Results: Mean maternal plasma free choline, dimethylglycine, and trimethylamine N -oxide (TMAO) concentrations increased during pregnancy by 49%, 17%, and 13%, respectively ( P < 0.005), whereas betaine concentrations decreased by 21% ( P < 0.005). Cord plasma concentrations of free choline, betaine, dimethylglycine, and TMAO were 3.2, 2.0, 1.3, and 0.88 times corresponding maternal concentrations at delivery, respectively (all P < 0.005). Maternal plasma concentrations of betaine, dimethylglycine, and TMAO ( r 2 = 0.19–0.51; P < 0.0001) at delivery were moderately strong, whereas maternal concentrations of free choline were not significant ( r 2 = 0.12; P = 0.06), predictors of cord plasma concentrations of these metabolites. Neither maternal dietary intake nor fetal genetic variants predicted maternal or cord plasma concentrations of choline and its metabolites. Conclusion: These data collectively indicate that maternal choline status, but not fetal genotype, influences cord plasma concentrations of choline metabolites. This trial was registered at clinicaltrials.gov as NCT02244684.